2018
DOI: 10.1371/journal.pone.0200214
|View full text |Cite
|
Sign up to set email alerts
|

Jailed in the mountains: Genetic diversity and structure of an endemic newt species across the Pyrenees

Abstract: The Pyrenees represent a natural laboratory for biogeographic, evolutionary and ecological research of mountain fauna as a result of the high variety of habitats and the profound effect of the glacial and interglacial periods. There is a paucity of studies providing a detailed insight into genetic processes and better knowledge on the patterns of genetic diversity and how they are maintained under high altitude conditions. This is of particular interest when considering the course of past climate conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 79 publications
6
14
0
Order By: Relevance
“…In agreement with structure and faststructure results for K = 2, all phylogenetic analyses showed a basal split in two clades corresponding to populations located east and west of an imaginary line located around the Segre river (~1°E (Charrier et al, 2014;Valbuena-Ureña et al, 2018). Overall, these results are consistent with the transverse breaks proposed by Wallis et al (2016) for numerous alpine taxa and support the idea that the fragmentation of ancestral distributions during glacial periods and the presence of Pleistocene refugia along mountain ranges has played a key role on the diversification not only of lowland species but also of montane and alpine organisms.…”
Section: Factors Structuring Genomic and Phenotypic Variationsupporting
confidence: 85%
See 2 more Smart Citations
“…In agreement with structure and faststructure results for K = 2, all phylogenetic analyses showed a basal split in two clades corresponding to populations located east and west of an imaginary line located around the Segre river (~1°E (Charrier et al, 2014;Valbuena-Ureña et al, 2018). Overall, these results are consistent with the transverse breaks proposed by Wallis et al (2016) for numerous alpine taxa and support the idea that the fragmentation of ancestral distributions during glacial periods and the presence of Pleistocene refugia along mountain ranges has played a key role on the diversification not only of lowland species but also of montane and alpine organisms.…”
Section: Factors Structuring Genomic and Phenotypic Variationsupporting
confidence: 85%
“…In agreement with structure and faststructure results for K = 2, all phylogenetic analyses showed a basal split in two clades corresponding to populations located east and west of an imaginary line located around the Segre river (~1°E). Similar east–west genetic splits have been reported for many other plant and animal species from the Pyrenean region (e.g., Alvarez‐Presas, Mateos, Vila‐Farre, Sluys, & Riutort, ; Bidegaray‐Batista et al, ; Charrier, Dupont, Pornon, & Escaravage, ; Milá, Carranza, Guillaume, & Clobert, ; Valbuena‐Ureña et al, ). This east–west split might be well explained by detailed geological reconstructions documenting heavily glaciated areas in the central part of the range and the likely presence of ice‐free refugia at its longitudinal extremes (Ehlers, Gibbard, & Hugues, ) that might have allowed montane/alpine species to survive glaciations and recolonize high elevations during interglacial periods (Charrier et al, ; Valbuena‐Ureña et al, ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The geographical distribution of maize landraces in SWF could also be the result of a diversifying selection. The occurrence of a genetical longitudinal gradient along the Pyrenees area as observed in this study has been reported for several species (47)(48)(49)(50). Gradients, such as altitude or longitude, play an important role in the Pyrenees, as they shape the existing proportion of suitable habitats along the mountains (48,49).…”
Section: Diversity and Genetic Structure Of Maize Landraces From The Swfsupporting
confidence: 71%
“…Gradients, such as altitude or longitude, play an important role in the Pyrenees, as they shape the existing proportion of suitable habitats along the mountains (48,49). Valbuena-Ureña et al (50) emphasized that longitude is an important gradient to take into account in the Pyrenees, because the influence of the Atlantic ocean provides cooler and wetter climate westwards than in Eastern areas, which are more influenced by the Mediterranean climate.…”
Section: Diversity and Genetic Structure Of Maize Landraces From The Swfmentioning
confidence: 99%